The road to abolition? : the future of capital punishment in the United States - Ogletree, Charles J.; Sarat, Austin (New York : New York University Press, 2016)
The essays featured in this book track the shift in attitudes in America toward capital punishment. They discuss the current debate over lethal injection as a case study on why and how the elimination of certain forms of execution might provide a model for the larger abolition of the death penalty.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on February 1, 2016).
Keywords: Capital punishment -- United States; True Crime; United States of America, USA; Ethical issues: capital punishment; Social services & welfare, criminology; Legal ethics & professional conduct